Prevalence and burden of obstructive lung disease in the urban poor population of Ottawa, Canada: a community-based mixed-method, observational study - Pakhale, Smita; Tariq, Saania; Huynh, Nina; Jama, Sadia; Kaur, Tina; Charron, Catherine; Florence, Kelly; Nur, Fozia; Bustamante-Bawagan, Margaret ( E; Bignell, Ted; Boyd, Robert; Haddad, Joanne; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Globally the burden of Obstructive Lung Diseases (OLD) is growing, however its effect on urban poor populations with the high prevalence of tobacco dependence is virtually unknown. The purpose of this project is to estimate the prevalence and burden of OLD in the urban, low-income populations of Ottawa, Canada. Methods The study presented in this paper was part of the PROMPT (Management and Point-of-Care for Tobacco Dependence) project; a prospective cohort study in a community-based setting (n = 80) with meaningful Patient Engagement from design to dissemination. Spirometry data, standardized questionnaires and semi-structured interviews from PROMPT were interpreted to understand the lung function, disease burden and social determinants (respectively) in this population. Results The prevalence of OLD among those who completed spirometry (N = 64) was 45–59%. Generic and disease-specific quality of life was generally poor in all PROMPT participants, even those without OLD, highlighting the higher disease burden this vulnerable population faces. Quality of life was impacted by two major themes, including i) socioeconomic status and stress and ii) social networks and related experiences of trauma. Conclusion The prevalence and disease burden of OLD is significantly higher in Ottawa’s urban poor population than what is observed in the general Canadian population who smoke, suggesting an etiological role of the social determinants of health. This urges the need for comprehensive care programs addressing up-stream factors leading to OLDs, including poor access and utilization of preventive healthcare addressing the social determinants of health. Trial registration ClinicalTrails.gov - NCT03626064 , Retrospective registered: August 2018.